INTERNET - BASED TELEMONITORING OF INTRAMYOCARDIAL ELECTROGRAMS - Hutten, H. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Purpose of the work: The potential of the Internet for worldwide transmission of intramyocardial electrograms (IMEGs) has been evaluated in order to provide permanent access to centers that are specialized in computerized signal processing.Materials and Methods: In 1992 the project CHARM (Computerized Heart Allograft Recipient Monitoring) has been started for monitoring the rejection in transplanted hearts. IMEGs are acquired by using a pacemaker system with capability for broad-bandwidth telemetry together with fractally coated electrodes in either epimyocardial or intraventricular position. The IMEGs are transmitted to a data acquisition station, where they are stored, analogue-to-digital converted and fed into the Internet after adding some clinically relevant data and encrypting. Internet transmission is mainly performed with the FTP protocol, but in some cases alternatively with e-mail. At the processing center, password secured data account has been installed for each connected hospital. Patient identification is achieved by utilizing the pacemaker identification code that is heading the transmission of the IMEGs to the data acquisition station. After signal processing and parameter extraction, complete patient reports are provided for the sending hospital.Results: Up to now more than 26.000 IMEG sequences each containing about 100 events have been sent to the processing station in Graz from 285 patients and 14 hospitals around the world. No transmission problems or erroneous transmission utilizing standard transmission protocols have been observed. It had been possible in any case to consider appropriately the firewall concept of the hospitals and adjust the transmission procedure to the requirements of the hospital. In the meantime computerized IMEG assessment is used not only for transplant monitoring, but for recipient monitoring and for hemodynamic assessment.Conclusion: Internet-based transmission of IMEGs to specialized centers for computerized signal processing has proven to be reliable and thus renders possible the establishment of cardiac telemonitoring. The center for signal processing can supply additional service for hospitals like data management in multicenter studies.